Insulin resistance in relation to clinical, endocrine and metabolic profile of infertile women with polycystic ovary syndrome (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
The objective of this study is to explore how hyperinsulinemia and insulin resistance relate to the clinical, endocrine and metabolic factors in the infertile women with polycystic ovary syndrome. This study was conducted on 121 consecutive infertile women with polycystic ovary syndrome attending the Infertility unit from January 2017 to December 2017. They were divided into two groups: insulin resistant and insulin sensitive. There was significant difference in body mass index and waist circumference between the two groups. Serum lipids were not associated with insulin resistance. Hyperinsulinemia was significantly associated with metabolic syndrome. Reducing body mass index and waist circumference may improve insulin resistance in infertile women with polycystic ovary syndrome. Screening the infertile women with polycystic ovary syndrome for hyperinsulinemia and insulin resistance and subsequent counseling is recommended to address the long-term risks of metabolic syndrome.